Impacts of climate change and land cover factor on runoff in the Coastal Chinese Mainland region - Song Song; Ziqiang Ye; Zhijie Zhou; Xiaowei Chuai; Rui Zhou; Jinwei Zou; Yi Chen (Geography and Sustainability)
The increasingly frequent storms pose significant threats to the sustainable development of coastal regions, particularly in densely populated and economically vibrant areas. Comprehending the dynamics and intricate mechanisms underlying runoff generation is crucial in the context of climate change and anthropogenic interference. Based on hydro-meteorological and land-use data from 1980 to 2018, this study investigates the runoff variation and its driving factors in the Coastal Chinese Mainland (CCM). The aims of this study are to reveal the temporal and spatial trends of runoff yield, to clarify the sensitivity of runoff in coastal cities to the integrated and individual parameters of climate change and anthropogenic interference, including precipitation (P), potential evapotranspiration (E0), and land cover factor (n), and to support the establishment of spatially tailored adaptation strategies. The results show that: (1) runoff has generally increased over the study period, particularly in regions such as the Yangtze River Delta, Shandong, and Guangxi, while it has decreased in western Liaoning and eastern Guangdong; (2) in the northern CCM with larger aridity index, the land cover factor plays a dominant role in runoff production, while in the wetter southern CCM, precipitation is more influential, and potential evapotranspiration mainly hinders runoff generation all over CCM; (3) urban expansion tends to negatively impact n, while the loss of grasslands and shrinkage of croplands tend to undermine the value of n. To facilitate the achievement of sustainable development goals in the CCM, it is imperative to introduce a more comprehensive and theoretical framework that encompasses the natural, technical, and social dimensions of human-water systems into traditional flood regulation and water resource management. This framework should promote interdisciplinary collaboration from an integrated perspective, to bridge the administrative and watershed boundaries, to effectively address the complex challenges posed by climate change and anthropogenic activities on runoff and water resources in coastal regions, and to enhance the realization of local sustainable development goals (UN SDGs).